Influência da eletroacupuntura craniana no equilíbrio de portadores de doença de Parkinson: estudo de configuração cruzada - Mehret, Rogério Romualdo (2019)
Introduction: the Parkinson’s Disease (PD) is considered the second most common neurodegenerative disease around the world, only behind Alzheimer Disease. PD is mainly characterized by motor symptoms such as tremor, bradykinesia, rigidity, and postural instability. The treatment for PD involves medicine, such as synthetic dopamine, surgical treatment, and alternative treatment. Unfortunately, pharmacological treatment tends to reduce its efficacy with the advancement of the disease, and alternative therapies have been sought as a complement to the treatment, being acupuncture one of the most used by patients with chronic PD. Within the existing techniques in acupuncture, electroacupuncture (EA), which is the electrical stimulation performed on the needles, and the cranioacupuncture or scalp acupuncture (SA), which is a technique for inserting needles into the scalp in already mapped areas of treatment, are the options most applied in patients with PD. Objective: to analyze the effects of EA in conjunction with the SA, on the balance of participants with PD, using as variables the center of pressure (COP) amplitude, the COP latency time, and the electromyography (EMG) latency time. Material and Methods: twenty-four individuals (64.59 ± 7.06 years) affected by PD of both genders, patients from the Parkinson's Association participated in the study. The participants were submitted to a pre-intervention evaluation with EA and SA, with 4 post-anterior balance perturbations, 2 performing a single task (ST) and 2 performing a double task (DT). At the end of the pre-intervention evaluation process, participants were submitted to an intervention with EA and SA, being that in one day they received intervention as an experimental group and another day as a placebo group. Immediately after this, the same pre-intervention process was repeated, now called post-intervention. The experimental intervention was performed in the SA points regarding balance, and the placebo intervention in SA points referring to the chest region. In this way, a total of 48 collections were performed. The data were analyzed using the Paired-T-Test, comparing the variables of the pre-intervention group with the variables of the post-intervention group. Results: There were reductions in the amplitude (p = 0.002) and the latency time (0.012) of the COP during the TS in the experimental group, and in the latency time of the EMG, there was a reduction in the accomplishment of the TS task in the experimental group for the right lateral gastrocnemius (p = 0.027) and also in the placebo group for the right soleus (p = 0.05). Another result in the EMG latency observed in the placebo and DT groups for the right medial gastrocnemius (p = 0.036) was the increase in EMG latency time after the disturbance. Conclusion: the results observed in the reduction of the amplitude of the COP, as well as in its latency time, as well as the reduction in the latency time of the EMG, suggest that there is an influence of the EA and SA on the balance of patients with PD.